The influence of rock mass and intact rock properties on the design of surface mines with particular reference to the excavatability of rock - Kramadibrata, Suseno (Curtin University, 1996)
The main aim of this Thesis is to examine how the rock mass and intact rock properties influence the excavatability of rock in surface mine. One of the most important decisions in the design of surface mine is the selection of mine equipment and plant. Now that increasing effort is being invested in the design and manufacture of continuous surface miners it is appropriate to examine how their performance can be related to the physical properties of the rock mass and intact rock.Over the years many attempts have been made to develop a means of assessing the excavatability of rock. Most of them are based on an empirical rating system whilst some authorities still propose the use of seismic velocity as a direct predictor of the rippability of a rock mass. On the other hand there are a number of classical models which have been developed to define the cutting force required at the pick or tooth of continuous miners.Whilst these methods have been applied with various degrees of success to the design of excavation systems there is no generally acceptable method of defining the excavatability or cuttability of a rock mass in terms of the machine power required to generate a particular rate of production.An attempt is made to overcome this deficiency by recording the intact and rock mass properties at Limestone quarry in Retznei, Austria; Openpit Gold Mines in Meekatharra and Mt Gibson of Western Australia and Openpit Coal Mine in Air Laya, Indonesia, where VASM-2D and Bucket Wheel Excavator O&K SchRs(800/1.2)15 or O&K S630 were in use in the first mine sites and Air Laya respectively to use this data to examine the relationships between the relevant dimensionless groups developed from a dimensional analysis of the problem.The dimensionless groups are obtained by examining the factors which influence the productivity of a surface miner. These include intact rock and rock mass properties, and machine power required for a particular rate of production and lead to the development of dimensionless groups namely, Rock Cuttability Index (RCI), Rock Mass Factor (RMF), Brittleness Index (BI), Rock Excavatability Index. The monitoring of machine power was carried out at Mt. Gibson and Air Laya mines.As a part of this study, field seismic tests were carried out at Mt. Gibson and Air Laya with the intention of seeking the most appropriate method of this type of test and analysis for excavation purposes. The test results indicate that borehole tests are the most promising and the output of seismic velocity obtained from a built-in program seismograph needs further thorough examination.The analysis of field data at all the sites proved that the most appropriate measure of discontinuities in the rock mass is the mean distance between discontinuities in a direction parallel to the cutting direction of the machine.Since the lateritic rock mass is different to other ordinary rock masses, a modified RMR is proposed. This is done by adjusting classification criteria on spacing and condition of discontinuity. The results proved that the discontinuity spacing obtained from the proposed method warrants wide application of the power cutting model developed.The RMR, Q-System and Excavatability Index are used to assess the performance of the continuous surface miners investigated. The results indicated that the Excavatability Index is the most acceptable criterion for the excavatability assessment.The outcome of this research has confirmed the significance of the RCI as a predictor of cutting performance of mechanical machines. The relationship between the RCI and REI can be used to good effect in analysing the performance of operating machines. A good example of this is given in the analysis of the performance of the BWE at the Mae Moh mine in Thailand.